PROTECTIVE MECHANISM IN CIVIL AND CRIMINAL MATTERS FOR VICTIMS OF DOMESTIC VIOLENCE - Lulciuc, Iulia; Franguloiu , Simona (International Journal of Legal and Social Order, 2024)
Domestic violence is a reality that is no longer ignored by the authorities who seek the most effective protective measures. The protection order is a protective mechanism designed to protect the victim by taking immediate measures to physically remove the aggressor and, under certain conditions, force him to follow detoxification programmes. The issuing of a protection order does not preclude the perpetrator from being held criminally liable when the conditions for this are met or from being given a custodial preventive measure. The protection order is a civil procedural measure, which removes a danger to the victim, and the preventive measure of preventive custody is provided for in criminal procedural law, which aims to remove a state of danger to public order.